Crystallization kinetics of charged PNIPAM microgels dispersions at low volume fractions - Bocanegra-Flores, J.; Haro-Pérez, C.; Reyes-Contreras, D.; Rojas-Ochoa, L. F. (Frontiers in Physics, 2022)
This work studies the kinetics of crystallization of charged microgels suspensions of Poly-N-Isopropylacrylamide (PNIPAM) at low ionic strength. The liquid-crystal transition is induced by suddenly decreasing the temperature of the microgel dispersion, and the crystallization process is monitored by measuring the temporal evolution of the static structure factor of the dispersion using light scattering. We find that the crystal growth rate, indicated by the temporal evolution of the crystallinity factor, strongly depends on the quenching temperature.